The effect of cigarette smoking and heated tobacco products on different denture materials; an in vitro study - Sara F. El Shafei; Ayman H. Amin; Eman G. Abdelghaffar; Sara Moataz; Fatma Makkeyah; Mohamed Shamel; Mahmoud Al Ankily (BMC Oral Health)
Abstract Purpose This study compares the effect of conventional cigarette smoke versus heated tobacco on the discoloration, surface roughness, and bacterial colonization of different oral prosthesis materials. Materials and methods A total of one hundred and twenty disc-shaped samples made of four different denture base materials were prepared to represent different denture bases to assess the surface roughness and biofilm formation; group (CA): conventional heat-cured acrylic resin (Acrostone, Egypt), group (FA): flexible acrylic resin (Valplast International Corp, USA), group (TA): heat-cured acrylic resin reinforced with titanium nanoparticles (TA nanoparticles, Nanogate, Egypt), and group (PA): 3D printed acrylic resin (Nexdent, The Netherlands). Another sixty samples of artificial and 3D printed teeth were used to assess the color change: conventional ready-made acrylic resin teeth (Acrostone, Egypt) and 3D-printed acrylic resin teeth (Nexdent, The Netherlands). Each group was further divided according to the smoking method into three subgroups (n = 10): the no-smoking exposure group (C), the conventional smoking exposure group (CS), and the heated tobacco exposure group (HT). A custom-made smoking device was used to perform the experiment. Six hundred cigarettes/heets representing 30 days of medium smoking behavior (20 cigarettes/day) were used. The surface roughness of the disc-shaped samples was measured before and after the experiment using the JITAI8101 surface roughness tester (Beijing Jitai Tech Detection Device Co., Ltd, China), and the color parameters were assessed before and after the experiment using VITA Easyshade Advance 4.01 (VITA shade, VITA made, VITA). Results The results showed that both conventional cigarette smoking and heated tobacco increased the surface roughness of the denture base disc samples. This change was statistically significant in all sample groups. Bacterial accumulation was also increased in all four denture base sample groups, with the heated tobacco causing greater bacterial accumulation than conventional cigarette smoke. Regarding the color change, conventional smoking caused a more significant color change than heated tobacco for both types of teeth used. Conclusion Both conventional smoke and heated tobacco affect dental materials adversely. Conventional cigarette smoking caused greater surface roughness and discoloration of the samples, while heated tobacco resulted in greater bacterial accumulation of study materials. Clinical implications Increase dentists’ and patients’ awareness of the effects of different types of smoke.